Prevalence of aggressive periodontitis in rural population around Vikarabad ( India) - An epidemiological study - B Prashanth; B Vijayalakshmi; T Muralikrishna; P Krishnajaneya Reddy; A Haritha; A Jayakumar (Wolters Kluwer Medknow Publications, 2013)
Introduction: The prevalence of aggressive periodontitis (AP) has been extensively studied globally. Limited information is available on the AP prevalence in the Indian population. Hence a survey of the susceptible students of educational institutions in villages around Vikarabad, Andhra Pradesh, India, was undertaken to give a more accurate prevalence of aggressive periodontitis in the population and relevant preventive and remedial measures could be taken. Materials & Method: A total o f9600 subjects were screened to estimate the prevalence of AP. Subjects with loss of attachment > 4mm were recalled to Department of Periodontics, Sri Sai College of Dental Surgery, Vikarabad for clinical and radiological confirmation. Results: From 9,600 students screened, 15 cases (LAP- 9, GAP-6) were found to be confirming to the diagnosis of AP, giving aprevalence of 0.16%. Conclusions: The prevalence rate of AP in the screened population is 0.16% and is similar to other prevalence studies in Andhra Pradesh and in consonance with several other global studies. The prevalence of aggressive periodontits is highly variable and controversial globally and needs concerted and systemic approach if this is to be settled.